Analysis of Trends and Risk Factors for Food Poisoning in Indonesia, 2022–2024 - Eka Wijayanti (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Food poisoning remains as serious public health issue in Indonesia, in addition to its health impacts, food poisoning also imposes an economic burden due to rising medical costs and decreased community productivity. This study aims to analyze trends in food poisoning cases and identify risk factors contributing to these incidents in Indonesia during the years 2022-2024. The study employed a quantitative descriptive design using secondary data sourced from reports by the Center for Drug and Food Policy Analysis of the Indonesian Food and Drug Supervisor Agency (PUSAKOM BPOM RI). Analysis was conducted using trend analysis, descriptive epidemiology, and bivariate and multivariate analysis to determine associated and dominant factors. The results indicate that food poisoning trends are fluctuating, with a significant increase in 2023 and a decrease in 2024, although the number of cases remains higher than in 2022. The distribution of cases indicates that regions with high population density, such as Jakarta, East Java, and West Jawa, tend to have a higher number of cases, which is associated with inadequate sanitation facilities. Risk factor analysis indicates that the food poisoning is influenced by various dynamic factors, with age being a relatively consistent influencing factor. Younger age groups tend to face a higher risk, influenced by consumption behaviors and low adherence to food safety principles. Therefore, strengthening education on Clean and Healthy Living Behaviors (PHBS), enhancing food safety oversight, and reinforcing surveillance systems are crucial steps in supporting food poisoning prevention efforts in Indonesia.